Application Of The Passing On The Right Exercise Model To Increase Vo2max Capacity - Akbar Sudirman; Ramli Ramli; Hezron Alhim Dos Santos (STKIP Muhammadiyah Kuningan, 2023)
This research aims to determine whether the Passing on the Right exercise is proven to increase the Vo2max capacity of Futsal Extracurricular Participants at SMKN 10 Makassar with a total sample of 23 male students. In addition, it can be used as reference material in sports coaching that the Passing on the Right exercise is a form of exercise that can be used as a form of exercise that can increase the Vo2max capacity of athletes. The method used in this research is the field experiment method. The treatment was given 18 times with a frequency of 3 times a week by the training program that had been prepared. To measure the Vo2max capacity, the researchers used a bleep test with a distance of 20 meters. Pretest data for the VO2Max ability of futsal extracurricular students at SMKN 10 Makassar with a total score of 841.30 ml/kg/min, an average value of 36.58 ml/kg/min with a standard deviation of 4.32 while the range is 15.10. The final test data (posttest) for the VO2Max capacity of futsal extracurricular students of SMKN 10 Makassar with a total score of 946.70 ml/kg/min, an average value of 41.16 ml/kg/min with a standard deviation of 4.22 while the range is 15.50. It can be seen that there is an increase in the Vo2Max capacity of futsal extracurricular students of SMKN 10 Makassar before and after treatment for 18 meetings with details three times a week, the average pretest value of 36.58 ml/kg/min to 41.16 ml/kg/min there is an increase of 4.58 ml/kg /min.